Cases in leadership - Rowe, W. Glenn; Guerrero, Laura (The Ivey casebook series, 2013)
Cases in Leadership, Third Edition is a unique collection of 32 real-world leadership cases from Ivey Publishing plus 16 practitioner readings from the Ivey Business Journal. The updated casebook helps business students gain a better understanding of leadership and enables them to be more effective leaders through their careers.